Me - R - Sakenfeld, Katharine Doob; (1940-...) (U.S.A, 2009)
The New Interpreter's Dictionary of the Bible (in five volumes) provides the best quality in contemporary biblical scholarship on a comprehensive range of topics from the Old and New Testaments, the Deuterocanonical books, and from contextual studies of the ancient Near East and the Greco-Roman worlds and their literatures. The dictionary contains maps, charts, and illustrations to further clarify the written material.
Keywords: Bible -- Dictionaries